Alternating self-administration sessions of cocaine and heroin impact drug-related motivation and vocalisations in rats - Kristian Adamatzky; Angharad C. Collins; Aldo Badiani; Bryan F. Singer (Psychopharmacology, 2025)
Rationale Animal models of addiction often study changes in motivation after repeated self-administration of a single drug. However, human users frequently consume multiple drugs, potentially altering their motivation and affective response. Objectives This study investigated how individual rats differentially self-administer cocaine and heroin, and whether motivation to take each drug was associated with affective states, as indicated by ultrasonic vocalisations (USVs). We also determined whether opioid antagonism (via naltrexone), which is known to decrease heroin-taking and associated USVs, also altered motivation and vocalisations for cocaine. Methods Male Lister Hooded rats, with surgically implanted catheters, self-administered cocaine and heroin on alternating days. Motivation was evaluated via drug intake escalation (fixed-ratio schedule), behavioural adaptation to dose reductions (behavioural economics), and progressive ratio breakpoints (with or without naltrexone). USVs were recorded and analysed using machine learning software (DeepSqueak). Results Rats escalated intake of both drugs during training. At the start of each session, rats rapidly self-administered cocaine or heroin; this drug-loading behaviour was associated with an increase in 50 kHz vocalisations. Rats altered their cocaine and heroin intake when drug doses decreased, and this was accompanied by reduced 50 kHz USVs. Lastly, naltrexone reduced progressive ratio breakpoints for heroin but not cocaine; naltrexone also decreased 50 kHz USVs for heroin (an effect which persisted). Conclusions Distinct patterns emerged in motivation and USVs between cocaine and heroin self-administration. Notably, USV frequency did not consistently align with motivation, especially when drug dosage changed. Future research may clarify this divergence.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).